Headache Characteristics in the Neurological Emergency Department: A Retrospective Study - Rimmele, Florian; Janke, Josephine; Kropp, Peter; Grossmann, Annette; Hamann, Till; Walter, Uwe; Jürgens, Tim P. (Frontiers in Neurology, 2021)
Introduction: The care of patients with headache in the emergency department (ED) represents a diagnostic and clinical challenge. Data on the prevalence and characteristics of headache patients in purely neurological EDs are sparse. The aim of the present study is to examine patient profiles with the cardinal symptom of headache in an academic neurological ED, to analyze correlations between headache characteristics and search for differences compared to the interdisciplinary ED. Methods: This retrospective cross-sectional study assessed all patients who presented to the ED of the Department of Neurology at Rostock University Medical Center between November 2013 and November 2016 with the main symptom of headache. Epidemiological, clinical, diagnostic data as well as key data regarding the care structure were recorded. Correlations between headache characteristics and diagnosis at discharge were analyzed and risk profiles were identified using binary logistic regression analysis. Results: 11,210 patients were included in the study, 1020 of whom suffered from headache as their cardinal symptom. The prevalence of headache as a cardinal symptom in the neurological emergency department amounted to 9.1%, with a female preponderance (64%) and an average age of 46 years. Primary headaches (40.1%) were the most frequent type, with migraine (73.4%) as the most common subtype. The second-largest group comprised secondary headaches (29%). Among the secondary headaches attributed to vascular diseases, 20.8% were associated with acute cerebral ischemia, 12.5% with subarachnoid hemorrhage, 14.6% with subdural hematoma and 6.3% with dissection of brain-supplying arteries. The concomitant symptoms nausea, photophobia, phonophobia, visual disturbance (p <0.001) and known history of migraine (p <0.001) were significantly correlated with the diagnosis of a primary headache leading to presentation in the ED. Higher age (p<0.001), a history of cardiovascular (p<0.001), respiratory (p<0.001), or oncologic disease (p<0.004), and trauma (p=0.001), as well as concomitant symptoms such as fever (p<0.001), aggravation by sneezing/coughing or Valsalva maneuvers (p=0.001) correlated positively with the diagnosis of secondary headache. Conclusion: This study comprehensively characterized a large collective of patients with the cardinal symptom of headache presenting to a purely neurology emergency department.